22 Pre-pregnancy counselling in cardiovascular disease: a service evaluation at the leeds teaching hospitals NHS trust (LTHT) 2014–2020. (4th June 2021) - Hamilton, Kate; Joy, Eleanor; Oliver, James; Gatenby, Kate; Winfield, Sarah; Everett, Thomas; Prestwich, Stewart; Halsey, Tiffany; English, Kate; Simms, Alexander
Abstract : Background: The European Society of Cardiology (ESC) 2018 guidelines for the management of cardiovascular disease during pregnancy 1 recommend women with cardiac disease receive pre-pregnancy counselling to facilitate informed decision making. Diagnoses are classified according to the mWHO score1, enabling a quantified risk of maternal morbidity and mortality. This estimated risk can be further adjusted based on individual anatomical, physiological and functional factors, allowing for tailored advice. Aim: To evaluate compliance with ESC guidelines1 on pre-pregnancy counselling at LTHT, including providing a quantified risk. Methods: Retrospective analysis of electronic records of 476 patients seen in the cardio-obstetrics clinic in LTHT 2014-2020. 241 met the inclusion criteria: 1. Known to LTHT cardiology services prior to first pregnancy 2. Cardiac diagnosis classifiable by mWHO class Results: Demographics of our patient cohort are in table 1 . 77.2% had congenital heart disease (CHD), and 22.8% acquired disease. 66.8% received pre-pregnancy counselling, 32.3% of these were given a quantified risk ( table 2 ). Rates of pre-pregnancy counselling were similar in CHD and acquired disease (67.6% vs 65.0%). 8 patients attended for pre-pregnancy counselling with no pregnancy to date. There was correlation between a higher mWHO class and a greater percentage of patients receiving pre-pregnancy counselling with risk quantification ( figure 1 ). Median age of first pregnancy was 27, irrespective of whether pre-pregnancy counselling occurred. No patients who became pregnant under age 18 received pre-pregnancy counselling, with the highest incidence of counselling occurring in those aged 35-39 ( figure 2 ). Discussion: Those at lower risk in pregnancy (mWHO I and II) were less likely to receive pre-pregnancy counselling, despite being advised in the ESC guidelines. The upward trend as risk increases is encouraging, however as ESC advise pregnancy in mWHO IV is contraindicated1, pre-pregnancy counselling is imperative to facilitate informed choice. ESC recommend pregnancy is first discussed in adolescence when becoming sexually active, so lower maternal age should not be prohibitive to receiving pre-pregnancy counselling. Whilst preferable for this to occur before transition to adult services, it should not be assumed that adult patients have received this information. Limitations include not accounting for patients who have not yet conceived (aside from 8 shown in figure 2 ), which in some cases could be the result of pre-pregnancy counselling. Furthermore, data collection from clinic letters omits any pre-pregnancy counselling that was not documented or pre-dated the use of electronic records. Conclusions: 66.8% of women with known cardiovascular disease were given pre-pregnancy counselling (target 100%). As such, a quality improvement initiative is being established to improve provision of pre-pregnancy counselling to all women of child-bearing age with cardiovascular disease. Conflict of Interest: None Reference: 2018 ESC Guidelines for the management of cardiovascular diseases during pregnancy. EHJ 2018;39 :3165–3241